PENGUATAN UMKM MELALUI BRANDING DAN PEMETAAN DIGITAL TERHADAP ANEKA KUE RAHMA DAN MBULAN SNACK DI DESA TEROS, LOMBOK TIMUR - Sapira, Nurul Jannati; Nawawi, Muhamad Satriya; Faradila, Jihan Dita; Mardita, Zelena Intan; Maharani, Luh Gede Anastasya; Afrilyadi, Dede; Kusminingsih, Titin; Zamzami, Baiq Sarah; Wibowo, Andrean Doni Satrio; Nadifa, Annisa; Salman, Ing (Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector, play a significant role in driving the Indonesian economy. However, many MSMEs face challenges in branding and digital marketing, which limit their market reach and competitiveness. This study focuses on two culinary MSMEs in Teros Village, East Lombok: Aneka Kue Rahma and Mbulan Snack. Although their products have good potential, both businesses rely on conventional marketing. Aneka Kue Rahma lacks a logo or visual identity, while Mbulan Snack's logo is unappealing and ineffective. Additionally, neither business has utilized digital platforms such as Google Maps. This research aims to strengthen the brand identity and enhance the digital presence of these two MSMEs through intensive mentoring. Using a qualitative method, data was collected through observation and interviews. Implemented solutions included designing a new, modern, and functional logo, creating promotional media such as banners, and listing the business locations on Google Maps with supporting information. The results show that both MSME owners responded positively to the solutions. Aneka Kue Rahma's owner feels more confident and professional with a logo and banner, while Mbulan Snack's owner received a new, more practical, and appealing logo. Their presence on Google Maps has increased visibility, making it easier for customers to find their locations and expanding their potential market reach. This program successfully delivered short-term changes while building a foundation for MSMEs to adapt and grow independently in the digital era.